Dinamika Komunikasi Politik dalam Pemilihan Kepala Daerah Kota Salatiga Tahun 2024 - Tunjung Wijanarka; Rizki Amalia Yanuartha; Dewi Kartika Sari; Benedict Alvianto Nazara (Jurnal Neo Societal, 2025)
This study seeks to explore the dynamics of political communication in the Salatiga City election. The author will use Bourdieu's ideas as a foundation to understand social reality and social media analysis as a campaign medium for mayoral and deputy mayor candidates of Salatiga City. Thus, the analysis can further describe how political communication of candidate pairs takes place. Also, how the understanding of the candidate pair in bringing plurality values in the campaign can be seen. Through a qualitative research method with an exploratory type, the results of the study show that there are candidate pairs who have advantages in different social capital and capital capital, which ultimately has implications for the political communication style of each candidate pair that is different from each other. In addition, to support the arguments and data presented, the author uses the Hybrid Media System (HMS) as one of the approaches to understand how different types of media – both old and new media – interact with each other and compete in the process of production, distribution, and consumption of information. This study concludes that the media plays an important role in the political communication process of each candidate which also utilizes the social capital and political capital owned by each candidate.